2013
DOI: 10.1210/jc.2012-3010
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA23a and MicroRNA23b Deregulation Derepresses SF-1 and Upregulates Estrogen Signaling in Ovarian Endometriosis

Abstract: MiR23a and miR23b are potential biomarkers of ovarian endometriosis. This study provides a novel approach for targeting the mechanisms controlling aberrant local estrogen biosynthesis in endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…However, Saare et al (2014) found that miR-200b was upregulated in such tissues. In addition, miR-20a plays an important role in the pathogenesis of ovarian endometriosis by suppressing NTN4 (Zhao et al, 2014), miR23a and miR23b are potential biomarkers of ovarian endometriosis (Shen et al, 2013), and miR196b targets c-myc and Bcl-2 expression, inhibiting proliferation and inducing apoptosis in endometriotic stromal cells (Abe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, Saare et al (2014) found that miR-200b was upregulated in such tissues. In addition, miR-20a plays an important role in the pathogenesis of ovarian endometriosis by suppressing NTN4 (Zhao et al, 2014), miR23a and miR23b are potential biomarkers of ovarian endometriosis (Shen et al, 2013), and miR196b targets c-myc and Bcl-2 expression, inhibiting proliferation and inducing apoptosis in endometriotic stromal cells (Abe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SF-1 plays an important role in the development and differentiation of steroidogenic tissues (73). miR-23a and miR-23b deregulation inhibits SF-1 and enhances estrogen signaling in ovarian endometriosis (74). Because miRs themselves are transcriptionally regulated by RNA polymerase II, they can also be regulated by some transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…В очагах эндометриоза присутствие SF-1 может приводить к увеличенной продукции эстрогенов [65]. Экспрессия SF-1 подавлялась сверх-экспрессией miR23a/b в эутопических эндометри-альных стромальных клетках и повышалась при ин-гибировании miR23a/b в нормальных эндометриаль-ных стромальных клетках [66]. Эти данные под-тверждались иммуногистохимически: уровень бел-ков SF-1 и StAR (steroidogenic acute regulatory protein) был значительно выше в эктопической эндометри-альной ткани по сравнению с нормальным эндоме-трием.…”
Section: гормональные факторыunclassified